Intracytoplasmic sperm injection versus conventional in vitro fertilization in unexplained infertility - Aya Iwamoto, M.S., M.D; Karen M. Summers, M.P.H; Amy Sparks, Ph.D; Abigail C. Mancuso, M.D (Elsevier, 2024)
Objective: To compare cumulative live birth rate (CLBR) and cost-effectiveness of intracytoplasmic sperm injection (ICSI) vs. conventional in vitro fertilization (cIVF). Design: Retrospective cohort study of cycles reported to the Society for Assisted Reproductive Technology Clinic Outcomes Reporting System. Setting: Society for Assisted Reproductive Technology (SART) member IVF clinics in the United States. Patient(s): Patients with unexplained infertility who underwent first autologous retrieval cycles between January 2017 and December 2019 with linked fresh and frozen embryo transfers through December 2021. Intervention(s): ICSI vs. cIVF. Main Outcome Measure(s): The primary outcome was CLBR, defined as ≤1 live birth from a retrieval cycle and all linked embryo transfers. Secondary outcomes included two pronuclear (2PN) per oocyte retrieved, miscarriage rate, and total number of transferred or frozen embryos per 2PN. Subsamples with and without preimplantation genetic testing for aneuploidy (PGT-A) were analyzed. Outcomes were adjusted for age, body mass index, number of oocytes retrieved, length of follow-up, and clinic ICSI use rate. Result(s): A total of 18,805 patients with unexplained infertility were included. No difference in CLBR was found among cycles without genetic testing (54.4% ICSI vs. 57.5% cIVF) and with PGT-A (47.6% ICSI vs. 51.8% cIVF). Intracytoplasmic sperm injection cycles without genetic testing had a higher miscarriage rate (16.4% vs. 14.4%) but no difference was seen in cycles with PGT-A (13.9% ICSI vs. 13.2% cIVF). Intracytoplasmic sperm injection cycles had a significantly lower ratio of 2PN per oocyte retrieved without genetic testing (59.7% vs. 60.9%) and with PGT-A (63.3% vs. 65.8%). The ratio of embryos transferred or frozen per 2PN was not significantly different in cycles without genetic testing (49.4% vs. 49.6%) or with PGT-A (54.2% vs. 55.2%). Total fertilization failure occurred in 216 patients (4%) who underwent cIVF and in 153 patients (1.1%) who used ICSI.Compared with cIVF alone, an estimated additional $11,011,500 was charged to patients for ICSI without genetic testing and $9,010,500 was charged to patients for ICSI with PGT-A over 2 years by Society for Assisted Reproductive Technology clinics. On the basis of total fertilization failure rates, 35 patients would require treatment with routine ICSI to avoid a single cycle of total fertilization failure with cIVF. Conclusion(s): Routine use of ICSI in unexplained infertility is not warranted due to the additional cost and lack of CLBR benefit.